Plasma Homocysteine as a Potential Marker of Early Renal Function Decline in IgA Nephropathy - Wang, Yan-Na; Xia, Han; Song, Zhuo-Ran; Zhou, Xu-Jie; Zhang, Hong (Frontiers in Medicine, 2022)
Hyperhomocysteinemia (HHcy) is very common among patients with chronic kidney disease (CKD), and related to the risk of cardiovascular events and mortality in these patients. However, the prevalence of HHcy in primary causes of CKD and its role in kidney disease progression are not well understood. In this study, we investigated the prevalence of HHcy in different CKD stages in 221 patients with IgA nephropathy (IgAN) and 194 patients with other primary glomerular diseases. We also evaluated the association of homocysteine (Hcy) (after adjusted for estimated glomerular filtration rate (eGFR)) with CKD progression event, defined as ESKD or 50% decline in eGFR, in a cohort of 365 patients with IgAN. The prevalence of HHcy was 67.9% (150/221), 53.5% (76/142), 51.5% (17/33) and 42.1% (8/19) in patients with IgAN, membranous nephropathy, minimal change disease, focal segmental glomerulosclerosis, respectively. The Hcy/eGFR ratio was significantly associated with pathologic features of IgAN, including the proportion of global glomerulosclerosis (r = 0.38, p < 0.001), the proportion of ischemia originated glomerular sclerosis (r = 0.32, p < 0.001), and the severity of tubular atrophy/interstitial fibrosis (r = 0.57, p < 0.001). Importantly, Hcy/eGFR ratio was an independent risk factor for CKD progression event (hazard ratio, 1.38; 95% confidence interval, 1.13 to 1.68; p = 0.002). The risk of CKD progression events continuously increased with the Hcy/eGFR ratio, but reached a plateau when Hcy/eGFR ratio was > 1.79. Our findings suggest that elevated Hcy/eGFR ratio may be an early marker of poor renal outcome in IgAN.